METAPHORICAL AND METONYMIC FIGURATIVE MEANING AND THEIR RENDERING IN TRANSLATION - B. N. Sulaymonov (Journals Park Publishing, 2024)
Metaphorical and metonymic figurative meanings, their differences, rendering and translations in two languages are discussed.
Keywords: transfer of meaning, metaphor, linguistic metaphor, artistic metaphor, bilingual dictionary, dictionary article.